Web Disclosure of Risk Management Practices in Malaysian Public Universities - Ahmad, Shahrul Nizam; Isa, Mohamad Yazid; Tapa, Afiruddin (HRMARS, 2016)
Enterprise risk management (ERM) has been the centre of focus for many private organizations especially financial institutions. Like their counterparts, non-profit organizations are not safe from risk exposures and it is more crucial when their funding originated from the public. There is little work done on the risk management implementation in the public organizations and research is needed to find out whether these organizations are serious in managing their risk and do they have a formal structure and framework to handle that.This study examines the existence of a formal risk management structure or framework in the Malaysian public universities. This is a preliminary investigation using websites as indicators, on the state of enterprise risk management implementation in Malaysian public universities.Based on the data gathered from a total of 20 public universities, this study found that most of them do have a formal risk management structure in place and some of them have even appointed a specific person (risk officer) specializing in handling the ERM activities of the universities.This paper would provide the foundation for more advanced research in the ERM implementation in non-profit organizations.